Prevalence of bovine brucellosis in central west region of Brazil - Oliveira, Murilo; Macedo Cintra, Acacio; Silva Mustafa, Vanessa (Pubvet, 2020)
Bovine brucellosis is a disease present worldwide, in Brazil it is endemic in all states. Because it is a zoonosis and causes socioeconomic problems, brucellosis has a particular focus on the diseases that affect farm animals whose Brazilian State wishes to eradicate. In a historical context, Brazil started its biggest step towards the eradication of the disease in mid-2004, where the National Program for the Control and Eradication of Brucellosis and Tuberculosis (PNCEBT) was implemented throughout the territory. Brazilian. To date, it was known that brucellosis was an endemic disease in several Brazilian states and that the Central West region of Brazil had a higher incidence of the disease among cattle and buffalo. After twelve years of program, this study aimed to evaluate the effectiveness in meeting its major goal, eradication of brucellosis. This paper presents the epidemiological evolution of brucellosis between 2012 and 2015 in the Midwest region of Brazil. The effectiveness of the program in the Central West region was regular when analyzed throughout the region, but there were weaknesses that need to be better observed so that the program of eradication and control of bovine brucellosis in Brazil does not stagnate. The states of Goiás and Mato Grosso have low prevalence, however based on the notifications was not noticeable the efficiency of the program for the eradication of the disease, since in every year the prevalence of the disease remained equivalent, while the Federal District and Mato Grosso do South presented a progressive decrease over the years analyzed. The PNCEBT has been effective in reducing cases of brucellosis, but with some obstacles to eradication, which is the main objective of the program. Underreporting and small producers who do not adhere to the program are points for improvement. In spite of it, it is important to emphasize that it is necessary researches that generate more accurate data so that, to evaluate the real effectiveness of the program, not only based on notified cases, but the circulation of the disease in the national herd.
Keywords: Cattle; brucellosis; eradication; PNCEBT